Improving Student Adjustment in Learning in the New Normal Era through Group Guidance Using a Behavioristic Approach with Modeling Techniques - Sandi, Alfun; Firman, Firman (International Journal of Applied Counseling and Social Sciences, 2023)
This study aims to: (1) analyze the differences in students' self-adjustment in learning the experimental group before and after attending the group guidance service using a behavioristic approach with modeling techniques, (2) analyzing the differences in student adjustment in learning the control group before and after attending the group guidance service. without special treatment, (3) analyzing the difference between students' adjustment in learning the experimental group and the control group after participating in group guidance services using a behavioristic approach with modeling techniques compared to the control group following group guidance without special treatment. The research method used is quantitative research. This type of research is Quasi Experiment Design. The population in this study was 218 students, using the Slovin formula to 141 students, then from the results of the overall data taken 22 students who were divided into 11 students for the experimental group and 11 students for the control group. Sampling used Simple Random Sampling. The research instrument used a Likert Scale model, the data were analyzed using the Wilcoxon Signed Ranks Test and the Kolmogorov-Smirnov with the help of SPSS version 20.00. The results showed that (1) there were differences in students' self-adjustment in learning the experimental group before and after taking group guidance using a behavioristic approach with modeling techniques, (2) there were differences in student adjustment in learning the control group before and after taking group guidance without special treatment. , (3) there are differences in student adjustment in learning the experimental group who followed group guidance using a behavioristic approach with modeling techniques compared to the control group who was given group guidance without special treatment.